The Influence of Social Media Marketing and the Ease of Use of Mobile Banking on Customer Loyalty with Customer Satisfaction as a Mediator in Mobile Banking Services “Digi by Bank BJB” - Alysha Prameswari Nurmalitasari; Aang Curatman; Siska Ernawati Fatimah (Journal of Social Research, 2026)
Many factors can affect customer loyalty, one of which is social media marketing. In addition to social media marketing, the ease of use of mobile banking can also affect customer loyalty. This study includes customer satisfaction as a mediating variable. The approach used in this study is quantitative. This is explanatory research. The population comprises 20,028 customers of Bank BJB who use "white Digi." The sample consists of 392 Bank BJB customers who use "white Digi," determined using the Slovin formula and purposive sampling techniques. Data were collected using questionnaires. Data analysis employed descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that: 1) social media marketing has a positive and significant effect on satisfaction; 2) the ease of use of "Digi by Bank BJB" has a positive and significant effect on customer satisfaction; 3) social media marketing has a positive and significant effect on customer loyalty; 4) the ease of use of "Digi by Bank BJB" has a positive and significant effect on customer loyalty; 5) satisfaction has a positive and significant effect on customer loyalty; 6) customer satisfaction mediates the relationship between social media marketing and customer loyalty; and 7) customer satisfaction mediates the relationship between the ease of use of "Digi by Bank BJB" and customer loyalty.